The little school system that could : transforming a city school district - Duke, Daniel Linden (State University of New York Press, 2008)
"The Little School System That Could is a story about transformation. In 1995, equipped with not much more than a vision of the quality education that urban students deserved, Tom DeBolt, the new superintendent of the Manassas Park School System, set into motion a series of reforms that transformed the district. By 2005 every school was accredited, passing rates on state tests had doubled, and the school system was attracting national attention. Daniel L. Duke examines the district's ten-year turnaround, from four organizational perspectives and addresses the critical role of professional and political leadership in overcoming the challenges of low morale, scarce resources, changing demographics, and dysfunctional school-community relations."--Jacket
Keywords: School improvement programs -- Virginia -- Manassas Park -- Case studies.; Education, Urban -- Virginia -- Manassas Park -- Case studies.; Educational change -- Virginia -- Manassas Park -- Case studies.; Enseignement -- Réforme -- Virginie -- Manassas Park -- Études de cas.; Enseignement en milieu urbain -- Virginie -- Manassas Park -- Études de cas.; EDUCATION -- Administration -- General.; Education, Urban; Educational change; School improvement programs; Virginia -- Manassas Park; Theory & Practice of Education.; Education.; Social Sciences.; Case studies.; Case studies